PENGARUH KEMAMPUAN, MOTIVASI, DAN PELUANG TERHADAP PRESTASI KERJA PEGAWAI NEGERI SIPIL DI PROVINSI RIAU - Jumiati Sasmita (Universitas Trisakti, 2012)
The research analyzed the public servants' work performance in Riau Province, Indonesia, with special emphasis on the influence of ability towards opportunity, motivation and work performance. Subsequently, the study analysed the influence of opportunity on wokers' motivation and their work performance and also the influence of motivation towards work performance. The study was conducted in the Riau Province among 500 randomly selected respondents. Data was analyzes using Structural Equation Modelling. The results showed that there was a strong influence between ability towards opportunity, motivation and work performance for the whole sample of Riau Province. Oportunity has a strong influence towards motivation for the whole sample of Riau Province. However, opportunity has no strong influence on the work performance in the Riau Province. There was no influence of the motivation variable towards work performance since the relationship between these two variables is insignificant. This is attributed to the fact that staff that performed well were not rewarded or appreciated. The theoretical contribution of this study is that the ability factor has strong influence towards opportunity, motivation and work performance which supports most of the earlier studies.The empirical findings can be used as guidelines for the Riau Government towards shaping and improving the existing policies and programs aimed at enhancing the public servants' work performance in the future.Keywords: Ability, Opportunity, Motivation, Work performance